Pengembangan Kreativitas Olahan Pangan Untuk Meningkatkan Nilai Ekonomi Kreatif Masyarakat Desa Kinnepen, Kec. Munte, Kab. Karo - Adetia Dara Ayu; Ayu Fitriana; Dinda Putri Agelia; Nur Haliza Pasha; Benni Icshanda Rahman (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2026)
The community service program implemented in Kineppen Village, Munte District, Karo Regency aims to optimize local orange harvests through outreach and training on orange marmalade production. The program's primary objective is to increase the economic value of the abundant local oranges by producing more profitable processed products. The program is implemented through three main stages: planning, implementation, and evaluation. Local women, particularly those from the elderly and prayer groups, are involved in the training and actively participate in the orange marmalade production process, packaging, and product labeling. Evaluation results indicate that participants are highly interested in producing orange marmalade independently, driven by the availability of materials and equipment. The program not only successfully increases community income but also reduces orange waste and encourages the development of a creative economy in the village. Thus, the program has a positive impact on the economic well-being of the local community and improves agricultural product management.